Change in profile of cutaneous manifestations of HIV after the advent of antiretroviral therapy: a retrospective analysis - Bwalya, Ireen C.; Lakhani, Som; Aldridge, Christian (International Journal of Research in Dermatology, 2021)
Background: To date, there has been no study conducted in Zambia to determine the prevalence of mucocutaneous conditions among HIV positive patients on antiretroviral therapy. Methods: The aim of the study was to determine the differences in cutaneous manifestations of HIV between HIV positive adult patients on antiretroviral therapy and antiretroviral naïve patients. Results: A total of 143 adult HIV/AIDS patients with dermatological manifestations, and fulfilling inclusion criteria, were included. Among the 58 patients on antiretroviral therapy, the most common dermatoses were hyper-pigmentation (18.97%), fungal dermatitis (17.24%) genital herpes (8.62%), papular pruritic eruption (8.62%), oral candidiasis (8.62%) and Kaposi’s sarcoma (6.9%). The most common dermatoses among the 85 antiretroviral naive patients were oral candidiasis (34.12%), herpes Zoster (17.65%), hyper pigmentation (8.24%), eosinophillic folliculitis (7.06%), abscesses (5.88%), herpes labialis (4.71%) and Kaposi's sarcoma (4.71%). Among patients in Stage III of HIV infection, the proportion of patients with infectious dermatoses was significantly greater than the proportion of patients with non-infectious dermatoses (47.5% versus 28.6%; p=0.036).The odds of having an infectious dermatosis were 28% lower for patients on antiretroviral therapy as compared to antiretroviral naive patients (p=0.001). Conclusions: There is a changing profile of muco-cutaneous conditions in HIV infected patients. Infectious dermatoses such as oral candidiasis and Herpes Zoster infections occur more frequently in antiretroviral naïve patients, as compared to patients on ART. Prevention of infectious dermatological conditions occurs with the use of ART.